Analisis Faktor-Faktor Penyebab Kesulitan Pembelajaran Daring Pada Peserta Didik SMA Negeri 1 Dompu - jannah, khurfatul; Muti’ah, Muti’ah; Al Idrus, Syarifa Wahidah (FKIP University of Mataram, 2024)
This study aims to find out what are the factors that cause online learning difficulties felt by students of SMA Negeri 1 Dompu. This type of research is a descriptive of qualitative research. The research population was 1006 students. The sampling technique was carried out using random sampling. Data collection uses a questionnaire that is empirically valid and reliable.. The technical analysis of the data used is descriptive statistics with percentages using Microsoft Excel. The results showed that online learning difficulties based on students' motivation factors were obtained 35%, students' learning interest factors were obtained 36%, students' family factors were obtained 43%, technical/network constraints factors were obtained 41% and students online learning implementation factors were obtained 42%. Based on the results of this study, it can be concluded that the factors causing online learning difficulties that are most felt by students in a row are family circumstances, the implementation of online learning, technical/network constraints, interest in learning, and finally learning motivation.